2013
DOI: 10.1159/000351862
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of the Retinal Nerve Fiber Layer in Multiple Sclerosis with Special-Domain Optical Coherence Tomography

Abstract: Background/Aims: Retinal nerve fiber layer (RNFL) thinning has been observed on histopathology and time-domain optical coherence tomography in many diseases of the central nervous system. In this study, with a higher resolution of spectral-domain optical coherence tomography (SDOCT), we detected RNFL changes in patients with multiple sclerosis (MS) in China, and compared RNFL thickness between eyes with and without optic neuritis (ON). Methods: In this retrospective, nonrandom case study, the patients were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 19 publications
1
17
0
1
Order By: Relevance
“…Reduced RNFL thickness in the absence of ON suggests possible subclinical episodes of ON or chronic axonal loss separate from acute attacks as a result of retrograde transsynaptic degeneration of retinal ganglion cells and their axons [18,19]. We also confirmed the results of previous studies that indicate a tendency of RNFL atrophy to be greater in ON-affected eyes than in unaffected eyes [20,21,22]. Previous studies reported that RNFL thickness was correlated with functional and structural measures of MS such as visual acuity, visual field, low-contrast letter acuity, contrast sensitivity, color vision, visual evoked potentials, brain atrophy assessed by magnetic resonance imaging and even quality of life [16,23,24,25,26].…”
Section: Discussionsupporting
confidence: 89%
“…Reduced RNFL thickness in the absence of ON suggests possible subclinical episodes of ON or chronic axonal loss separate from acute attacks as a result of retrograde transsynaptic degeneration of retinal ganglion cells and their axons [18,19]. We also confirmed the results of previous studies that indicate a tendency of RNFL atrophy to be greater in ON-affected eyes than in unaffected eyes [20,21,22]. Previous studies reported that RNFL thickness was correlated with functional and structural measures of MS such as visual acuity, visual field, low-contrast letter acuity, contrast sensitivity, color vision, visual evoked potentials, brain atrophy assessed by magnetic resonance imaging and even quality of life [16,23,24,25,26].…”
Section: Discussionsupporting
confidence: 89%
“…Results revealed a significant reduction in RNFL thickness (P = 0.011) only in the temporal quadrant. Other studies have found RNFL thinning in all quadrants, 110 temporal, and inferior quadrants 111 and in the superior and inferior quadrants, 112 which correlated to their corresponding visual field regions. 14 Gundogan et al 109 also assessed the retinal functional status of these patients using pattern VEP, which showed significant delays in P100 latency in 60 and 15-min arc checks (Po0.001) in patients with MS, however, P100 amplitude was only significantly reduced in 60-min arc checks.…”
Section: Ms Without Onmentioning
confidence: 63%
“…The authors reported that each year of follow‐up was associated, on average, with a 2‐µm decrease in RNFL thickness. Gundogan et al investigated MS patients with no previous visual symptoms and revealed a significant reduction in RNFL thickness ( P = 0.01) only in the temporal quadrant, while other studies have found RNFL thinning in all RNFL quadrants or in the superior and inferior quadrants, which correlated to the corresponding visual fields . Two further studies reported progressive neuronal and axonal loss of RGC in NON eyes of MS patients .…”
Section: Introductionmentioning
confidence: 97%